Structure, relationships and history of drug use in families of crack cocaine users - Maycon Rogério Seleghim; Magda Lúcia Félix de Oliveira (Universidade Federal de Goias, 2014)
The objective of this study was to analyze the structure, relationships and history of drug use in families of crack cocaine users. It is a cross-sectional study, based on the General Systems Theory and on the genogram. The sample comprised 15 families of crack cocaine users cared for by a specialized drug dependency service in the state of Paraná, Brazil, throughout the month of May 2011. We conducted semi-structured interviews and created genograms, which were grouped according to similarities. For the most part, participants were mothers with low education levels. Regarding family structure, we found most people belonged to the second generation, constituting nuclear families, and to the first generation, with different family configurations. Relationships and family history of drug use followed the generational structural differences. We conclude that the characteristics of crack cocaine users' families seem to follow the changes in social structure observed over the last few decades. doi: 10.5216/ree.v16i3.21282.